KODE ETIK PENYIARAN BENTUK TANGGUNG JAWAB SOSIAL PENYIARAN DI INDONESIA - Topan Bilardo; Indah Putri (SYMBOLE, 2025)
Mass media has three functions, namely education, information and entertainment. If we look at its function, the media really provides new innovations to society. These three functions not only have positive effects, but in fact mass media also has negative effects on society. With the function of mass media and its effects that can change attitudes, behavior and social order, mass media or broadcasting must have good control and be wise in providing information to the public. Every broadcasting in Indonesia must be regulated and controlled in presenting information. There are binding rules so that every element involved in presenting news or information must use it as a reference and guideline. The social responsibility of broadcasting that is currently expected is freedom of responsibility, with the understanding that media people or journalists are free to convey various information to the public, but are responsible for thinking about the improvement and morality of society. The role of broadcast media in Indonesia has a responsibility to the public by implementing the provisions of the Broadcasting Law and more specifically implementing P3SPS with high commitment, in order to realize broadcast quality and have a positive effect on society.